A note on merger and acquisition evaluation - Benjamin Furlan; Harald Oberhofer; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2014)
This note proposes the continuous treatment approach as a valuable alternative to propensity score matching for evaluating economic effects of merger and acquisitions (M&A). This framework allows to consider the variation in treatment intensities explicitly, and it does not call for the definition of cut-off values in traded ownership shares in order to construct a binary treatment indicator. We demonstrate the usefulness of this approach using data from European M&As and by relying on the example of post-M&A employment effects.
Keywords: C21; G34; L25; 330; Merger and acquisition evaluation; continuous treatment models; generalized propensity score matching; employment effects